AUDIENCE AWARENESS IN THE WRITTEN DISCOURSE OF SUDANESE EFL UNIVERSITY LEARNERS - Ali Ahmed Osman Zakaria; Abdel Rahim Hamid Mugaddam (University of Kuningan, 2014)
Abstract: The study investigates the written discourse of the Sudanese EFL university learners to evaluate and assess their awareness of the audience to whom they write. The analytic descriptive approach is adopted to achieve the aims of the study. The subjects of the study consisted of 50 Sudanese EFL students drawn from Faculty of Arts at Alneelain university. Three tools were employed for data collection: a writing test, a questionnaire and an interview with the students. Results showed that the written discourse produced by Sudanese EFL students did not reveal an awareness of the audience with whom they communicate. The students did not succeed to make assumptions of what their audience already know and what they expect to find in the texts being written. They held fragmentary knowledge on the concept of audience awareness. Accordingly, the students were not able to prepare and edit texts which keep and stimulate their audience – they were not able to depend on lexical and structural variation to produce proper and effective writing. Furthermore, results indicated that students were not able to attach unity and coherence to the texts they produced. Their organizational skills were very poor. To help the students develop the concept they hold on audience awareness, writing instructors and syllabus designers need to put special emphasis on the importance of audience awareness as a factor which is essential for effective writing. Keywords: audience awareness, communicative setting, language proficiency, discourse competence